Which Teacher-Student Interaction Triggers Students’ Uptake - Clara Herlina Karjo (Humaniora, 2015)
The pattern of interaction between the teacher and the students will determine the students’ uptake (i.e. the students’ incorporating correction into an utterance of their own). This paper examines the type of teacher-student interaction which will likely trigger the students’ uptake. The data was taken from the recordings of 10 non-native English lessons at university level and different types of subjects (literature, grammar, discourse, semantics, and classroom management). 500 minutes of lessons were transcribed and 50 focus on form episodes were chosen to be analyzed. The study revealed that the dominant type of interaction was reactive focus on form which was followed by metalinguistic feedback.